Interactions between methodological and interindividual variability: How Monetary Incentive Delay (MID) task contrast maps vary and impact associations with behavior. Issue 5 (22nd March 2021) - Demidenko, Michael I.; Weigard, Alexander S.; Ganesan, Karthikeyan; Jang, Hyesue; Jahn, Andrew; Huntley, Edward D.; Keating, Daniel P.
Abstract: Introduction: Phenomena related to reward responsiveness have been extensively studied in their associations with substance use and socioemotional functioning. One important task in this literature is the Monetary Incentive Delay (MID) task. By cueing and delivering performance‐contingent reward, the MID task has been demonstrated to elicit robust activation of neural circuits involved in different phases of reward responsiveness. However, systematic evaluations of common MID task contrasts have been limited to between‐study comparisons of group‐level activation maps, limiting their ability to directly evaluate how researchers' choice of contrasts impacts conclusions about individual differences in reward responsiveness or brain‐behavior associations. Methods: In a sample of 104 participants (Age Mean = 19.3, SD = 1.3), we evaluate similarities and differences between contrasts in: group‐ and individual‐level activation maps using Jaccard's similarity index, region of interest (ROI) mean signal intensities using Pearson's r, and associations between ROI mean signal intensity and psychological measures using Bayesian correlation. Results: Our findings demonstrate more similarities than differences between win and loss cues during the anticipation contrast, dissimilarity between some win anticipation contrasts, an apparent deactivation effect in the outcome phase, likely stemming from the blood oxygen level‐dependent undershoot, and behavioral associations that are less robust than previously reported. Conclusion: Consistent with recent empirical findings, this work has practical implications for helping researchers interpret prior MID studies and make more informed a priori decisions about how their contrast choices may modify results. Abstract : This manuscript systematically evaluates common task contrasts of the Monetary Incentive Delay task and considers within‐study differences of mean‐level (or group level) activation maps, their regional associations, and effectiveness in predicting substance use and socioemotional behaviors in young adults. Our findings demonstrate more similarities than differences between positive and negative cues during the anticipation contrasts, dissimilarity between some positive anticipation contrasts, a robust deactivation effect in the outcome phase, and ROI‐behavior associations that are less robust than previously thought.